Implementation Of Job Analysis In Collega Group - Oktavia, Yolanda; Nirmalasari, Healthy (Pusat P2M Politeknik Negeri Batam, 2024)
This research aims to conduct a job analysis at Collega Group to understand the duties and responsibilities of each job by compiling a standardized job description and job specification document. job analysis is carried out using a combined method, namely the questionnaire method and the interview method used to collect primary data, which is then analyzed using the Miles and Huberman model by reducing data, presenting data and drawing conclusions/verification. The results of this job analysis process are 39 job description documents and job specifications that can be used as a basis for recruitment, training, and evaluation of employees in the future, with the hope of increasing efficiency in human resource management and quality of service to consumers at Collega Group. Despite limitations in data collection, this research makes a significant contribution in strengthening the company's human resource management.